2013
DOI: 10.3233/jhd-130051
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Huntington's Disease: A Comparative Study Investigating the Impact for those with Pre-Manifest and Early Manifest Disease, and their Partners

Abstract: Background: Given the multifaceted nature of this inherited neurodegenerative condition, typically affecting adults in mid-life, it is perhaps not surprising that studies indicate poorer Health Related Quality of Life (HrQoL) in those with the gene-expansion and, by association, in their families.Objective: This study aimed to extend the current literature by exploring specific life domains, including at an earlier disease stage than usually reported in the HRQoL literature, and in a subgroup of gene-negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
60
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 0 publications
6
60
0
1
Order By: Relevance
“…The TFC was the only factor significantly associated with HRQoL. This finding is in line with previous studies [12, 39, 40]. One possible explanation may be that improving HRQoL through the use of ATC requires more than access to devices.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The TFC was the only factor significantly associated with HRQoL. This finding is in line with previous studies [12, 39, 40]. One possible explanation may be that improving HRQoL through the use of ATC requires more than access to devices.…”
Section: Discussionsupporting
confidence: 91%
“…Cognitive impairment in HD can have a detrimental effect on health-related quality of life (HRQoL) through affecting ability to work and partake in leisure activities, interpersonal relationships, and ability to maintain self-care [10–13]. Two studies on HD have identified impaired cognitive function as the strongest negative determinants of HRQoL [12, 14]…”
Section: Introductionmentioning
confidence: 99%
“…There is currently no cure or way to stop the progression of HD. Thus, patient care focuses on the management of symptoms and improvement of the quality of life 10, 11, 12, 13. The HD mutation is an obvious target for therapeutic intervention based on gene silencing or genome editing, because it is at the top of all pathological cascades.…”
Section: Introductionmentioning
confidence: 99%
“…The Apathy Scale (AS) [20] is the only self-rated measure dedicated exclusively to apathy that has been used in HD to date. Other self-rated scales such as the Frontal Systems Behaviour Scale (FrSBe) have been used which contain a separate subscale on apathy [21] but cover the issue in less detail. The AS requires the patient's companion to rate the extent of apathetic symptoms experienced by the patient.…”
Section: Introductionmentioning
confidence: 99%